2006
DOI: 10.1038/oby.2006.184
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Trait Locus on Chromosome 18q for Physical Activity and Dietary Intake in Hispanic Children

Abstract: Objective: Genetic components of energy homeostasis contributing to childhood obesity are poorly understood. Genome scans were performed to identify chromosomal regions contributing to physical activity and dietary intake traits in Hispanic children participating in the VIVA LA FAMILIA Study. Research Methods and Procedures: We report linkage findings on chromosome 18 for physical activity and dietary intake in 1030 siblings from 319 Hispanic families. Measurements entailed physical activity by accelerometry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
4
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 46 publications
4
104
4
4
Order By: Relevance
“…This is lower than the 78 % observed earlier by Joosen et al , but is congruent with the 55 % observed in a twin study with subjective (Mustelin et al 2009) measures of physical activity, but higher than the 37 % of the twin study with objective measurements (den Hoed et al 2013). In concordance with earlier studies, the present study suggests that the residual variance (43 %) is likely accounted for by unique environmental factors (AE model) (Cai et al 2006;Joosen et al 2005;Mustelin et al 2009;den Hoed et al 2013). However, a role for common environmental factors (ACE model) cannot be excluded, as approximately 262 twin pairs are required to detect such an effect with an additive genetic effect of 60 %, a confidence level of 0.05 and a power of 80 % (Visscher et al 2008).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is lower than the 78 % observed earlier by Joosen et al , but is congruent with the 55 % observed in a twin study with subjective (Mustelin et al 2009) measures of physical activity, but higher than the 37 % of the twin study with objective measurements (den Hoed et al 2013). In concordance with earlier studies, the present study suggests that the residual variance (43 %) is likely accounted for by unique environmental factors (AE model) (Cai et al 2006;Joosen et al 2005;Mustelin et al 2009;den Hoed et al 2013). However, a role for common environmental factors (ACE model) cannot be excluded, as approximately 262 twin pairs are required to detect such an effect with an additive genetic effect of 60 %, a confidence level of 0.05 and a power of 80 % (Visscher et al 2008).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, evidence from twin studies with objective measures of physical activity suggests a minor genetic effect in children (Fisher et al 2010), a high level of heritability (h 2 = 78 %) in young adults , whereas a heritability of 35 % was estimated in a large sample of women ranging from 18 to 80 years of age (den Hoed et al 2013). Studies aiming to identify genetic variants that are associated with objective measures of HPA are scarce (Cai et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study of Hispanic children that measured physical activity using accelerometry suggested that a mutation of MC4R , which colocalized to a QTL for chromosome 18q, was associated with activity levels. 64 However, MC4R did not colocalize to any of the QTL identified in the larger human GWAS 66 or in any of the identified animal QTL. Thus, while MC4R shows promise as a candidate gene, further evidence is needed.…”
Section: Potential Candidate Genes For Physical Activitymentioning
confidence: 88%
“…In an earlier, smaller genome-wide scans in humans, Cai and coworkers 64 identified one highly significant QTL on chromosome 18q associated with sedentary activity in Hispanic American children. Colocalizing within this QTL, the authors suggested that the melanocortin-4 receptor ( MC4R ) gene was a potential gene linked with physical activity in their cohort.…”
Section: Genomic Locations Associated With Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation